Management of a Polytrauma Patient with L4 Bony Fracture-Dislocation, Multi-Level L1-L3 Flexion-Distraction (Bony Chance) Injuries, Lateral Compression III Pelvic Injury, and Lower Extremity Fractures - Bienvenido Leo Antonio Caro; Dave Anthony Dizon (Philippine Journal of Orthopaedics)
This is the first documented case of a neurologically impaired polytrauma patient with multiple bony Chance injuries, a windswept pelvis, and lower extremity fractures.